Human givens rewind trauma treatment: description and conceptualisation. Issue 2 (2nd July 2019) - Adams, Shona; Allan, Steven
Abstract : Purpose: Human Givens (HG) Rewind technique is a graded trauma-focused exposure treatment for post-traumatic stress disorder and trauma. The purpose of this paper is threefold: first, to describe the technique; second, to provide an outline of its potential benefits; and third, to present some preliminary evidence. Design/methodology/approach: This paper provides an overview of HG therapy and describes the stages of HG Rewind trauma treatment and its potential benefits. Similarities and differences between Rewind and other Cognitive Behavioural Therapy techniques are explored. Possible underlying mechanisms are discussed. Findings: Preliminary evidence suggests that Rewind could be a promising trauma treatment technique and that HG therapy might be cost effective. The findings highlight the need for further research and a randomised controlled trial (RCT) on Rewind is warranted. Practical implications: During the rewind technique, the trauma does not need to be discussed in detail, making treatment potentially more accessible for shame-based traumas. Multiple traumas may be treated in one session, making it possible for treatment to potentially be completed in fewer sessions. Social implications: This UK-based treatment may be cost effective and make treatment more accessible for people who do not want to discuss details of their trauma. Originality/value: This is the first description of HG Rewind in the peer-reviewed literature. Alternative explanations for mechanisms underlying this trauma treatment are also presented.